Giovani, genere e partecipazione nelle aree marginali meridionali | Youth, Gender, and Participation in Southern Marginal Areas - Leone, Stefania; Orio, Andrea (SocietàMutamentoPolitica, 2025)
The article explores the gender condition in inner and rural contexts of some regions of Southern Italy and the responses coming from participatory practices and social projects against inequalities and forms of discrimination. Through interviews with young women living in these areas and case studies of youth associations, on the one hand the obstacles and the limits of traditional models rooted in fixed roles and stereotyped behaviors are revealed; on the other hand, transformative practices and spaces emerge in which young people redefine gender-related expectations and imagine alternative social models. The results are discussed through an intersectional lens, highlighting how gender interacts with the spatial and cultural dimensions of internal areas in shaping youth experiences. Participatory forms follow individual and collective paths based respectively on the value of example and sharing. The paper aims to enrich the debate on how gender and the youth component produce specific challenges and opportunities related to the transformative potential of participation in promoting egalitarian and inclusive conditions, relationships and dynamics in conservative contexts refractory to change and innovation.